The Fulfillment of Need Main Character Lina in the Novel between Shades of Gray by Ruta Sepetys - Sobari, Saniyyah Maulidya; Sukmawaty, Fenty; Saprudin, Saprudin (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
The title of this research is the fulfillment of Need Main Character Lina in the Novel Between Shades of gray by Ruta Sepetys. Lina is the main character in the novel who tries to fulfilled her needs when she and her family were deported by the Soviet red army. This research aims to find out how Lina fulfilled her needs through the theory of the hierarchy of needs fulfillment by Maslow. The method used in this research is descriptive qualitative method, in which the researcher presented the data in a descriptive form or the data itself is not presented in the form of numbers. The approach used is a literary psychology approach while researchers use reading and note-taking techniques as data collection techniques. The final results of this study show that Lina has succeeded to fulfilling her needs according to hierarchy of needs fulfillment theory. Keywords: Hierarchy of Needs Fulfillment, Main Character, Abraham Maslow